PEMODELAN SPASIAL PERUBAHAN TUTUPAN LAHAN DAN PREDIKSI TUTUPAN LAHAN KECAMATAN TELUK AMBON BAGUALA MENGGUNAKAN CA-MARKOV - Somae, Glendy; Supriatna, S; Rakuasa, Heinrich; Lubis, Aufar Raynanda (Universitas Muhammadiyah Gorontalo, 2023)
Teluk Ambon Baguala District, is one of the sub-districts in Ambon City which has experienced a significant increase in population. Along with the increasing population, the need for residential, infrastructure and industrial land is increasing. This will certainly have an impact on the conversion of other cover to uncontrolled built-up land, environmental damage and natural disasters. This study aims to analyze land cover changes in Teluk Ambon Baguala District in 2014, 2018, 2022 and predict land cover models in 2026, 2030 and 2034. The driving factors used are slope, land height and distance from the road. This study uses the CA-Markov method to predict future land cover. The results of the analysis of changes and predictions of land cover in 2014, 2018, 2022, 2026, 2030 and 2034 show that built-up land continues to increase in area along with increasing population and the high demand for built-up land which is increasing.